Developemetn Calculation Tool for Multi-Objectivein Economic Compensation in Electrical Distribution Network - Le, Duc Tung; Nguyen, Huu Hieu; Van, Ngoc Thang; Pham, Qui Nin (Old Journal, 2018)
The power loss reduction has been one of the primary missions of electricity distribution companies. Currently, on distribution network, there are two technical methods which are employed to reduce power losses: load compensation and optimal network opening. In this paper, the authors proposed multi-objective optimal algorithm allows evaluating the effectiveness of the solutions to the different conditions. This algorithm is established in the Matlab environment. This tool is used to modeling and calculation the distribution network IEEE-16 buses with two objectives: minimum calculating cost when installing, operating capacitor and maximum amount of money gained from reduction of power losses when installing capacitor. The results have demonstrated the validity and feasibility of the proposed method.